2020
DOI: 10.1016/j.dib.2019.104929
|View full text |Cite
|
Sign up to set email alerts
|

Data on cytotoxic and antibacterial activity of synthesized Fe3O4 nanoparticles using Malva sylvestris

Abstract: The biosynthesis of materials using medicinal plants can be a low-cost and eco-friendly approach due to their extraordinary properties. Herein, we reported a facile synthesis of Fe3O4 nanoparticles using Malva sylvestris. The surface morphology, functional groups, and elemental analysis were done to characterize the synthesized nanoparticles. The cytotoxicity performance of the synthesized nanoparticles was analyzed by exposing nanoparticles to MCF-7 and Hep-G2 cancer cell lines through MTT colorimetric assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 4 publications
2
30
1
Order By: Relevance
“…Indeed, as shown in Figure 2, the type 1 fimbriae which is sensitive to mannose is blocked by fructose and PACs block the others type 1 fimbria mannose-resistant: this reduces the adhesion capacity of the bacteria and enables the bladder to "flush out" the UPs when urine is expelled (Sihra et al, 2018). In addition, randomized controlled trials have shown that cranberry juice can reduce the (Saratale et al, 2019;Sheikh and Ishnava, 2020); CuO (Ramesh et al, 2020) Caesalpinia nuga (L.) (Fatimah et al, 2020); Au (Chan et al, 2020); MgO and ZnO (Priya et al, 2020) Lamiaceae P. vulgaris Ag (Surya et al, 2016; CuO (Dinesh et al, 2020); ZnO (Manokari et al, 2017) (Mousavi et al, 2020); Ag (Feizi et al, 2018;Esfanddarani et al, 2017); CuO (Taran et al, 2017) Meliaceae Azadirachta indica A.…”
Section: Use Of Plants Extract Phytochemicals and Green-synthetized Nanoparticles Against Utis And Upsmentioning
confidence: 99%
“…Indeed, as shown in Figure 2, the type 1 fimbriae which is sensitive to mannose is blocked by fructose and PACs block the others type 1 fimbria mannose-resistant: this reduces the adhesion capacity of the bacteria and enables the bladder to "flush out" the UPs when urine is expelled (Sihra et al, 2018). In addition, randomized controlled trials have shown that cranberry juice can reduce the (Saratale et al, 2019;Sheikh and Ishnava, 2020); CuO (Ramesh et al, 2020) Caesalpinia nuga (L.) (Fatimah et al, 2020); Au (Chan et al, 2020); MgO and ZnO (Priya et al, 2020) Lamiaceae P. vulgaris Ag (Surya et al, 2016; CuO (Dinesh et al, 2020); ZnO (Manokari et al, 2017) (Mousavi et al, 2020); Ag (Feizi et al, 2018;Esfanddarani et al, 2017); CuO (Taran et al, 2017) Meliaceae Azadirachta indica A.…”
Section: Use Of Plants Extract Phytochemicals and Green-synthetized Nanoparticles Against Utis And Upsmentioning
confidence: 99%
“…Activity. Since the investigation of antibacterial and antifungal properties is a vital issue in biochemistry and pharmacy, so far a significant group of researchers has insisted on this, and therefore the preliminary element of their articles was to determine these properties [63,64]. It is proven that Kombucha has a supreme antimicrobial effect on a wide range of microorganisms [65] and so far many evaluations have been carried out to demonstrate the inhibitory performance against plenty of microorganisms including Gram-negative and Gram-positive bacteria [30].…”
Section: Antimicrobial and Antifungalmentioning
confidence: 99%
“…e minimum inhibitory concentration (MIC) results [63] of antimicrobial activity for Kombucha beverages are summarized in Table 3. Since MIC values were in the limitation of 9.765 μg/mL to 312.5 μg/mL, all the samples could be considered as antimicrobial agents in comparison to the standard antibiotics Amracin (for bacteria) and Nystatin (for yeasts) [53].…”
Section: Antimicrobial and Antifungalmentioning
confidence: 99%
“…Over the last century, the use of vegetation in medication, hematology, oncology, and immunology has affected the identity of natural composites: codeine, taxol, vinblastine, morphine, and cocaine, among others. e results of several studies have shown that Malva extract contains different compounds, including phenolic derivatives, flavonoids, terpenoids, catalase enzymes, sulfite oxidase, fatty acids, and certain strolls (specifically essential fatty acids such as omega-3 and omega-6), beta carotene, and vitamins C and E, which have anti-inflammatory and antioxidant properties [12][13][14][15]. erefore, it can protect the kidney against injuries due to renal toxicity resulting from the cisplatin and vanadium system [16].…”
Section: Introductionmentioning
confidence: 99%